Closed reduction in late-detected developmental dysplasia of the hip: Indications, results and complications. (August 2018) - Wicart, P.; Seringe, R.; Glorion, C.; Brassac, A.; Rampal, V.
Purpose: The aim of the study was a review of the literature in order to evaluate the results and complications of closed reduction in late-detected developmental dysplasia of the hip (DDH). Methods: This study consisted of an analysis of the literature relative to late-detected DDH treatment options considering hip congruency, rates of re-dislocation and of avascular necrosis. Results: Gradual closed reduction (Petit-Morel method) appears to be an effective method concerning joint congruency restitution. Dislocation relapse and avascular necrosis are more efficiently prevented with closed versus open reduction. The tendency for spontaneous correction of acetabular dysplasia decreases if closed reduction is performed after 18 months of age. Patient age at the beginning of traction should be considered for the prognosis, with a lower rate of satisfactory results showing after the age of 3 years. Conclusion: In our opinion, the Petit-Morel method is a suitable treatment option for children aged between six months and three years with idiopathic DDH.